Two homozygous adjacent novel missense mutations in DYSF gene caused dysferlinopathy due to splicing abnormalities - Wang, Lun; Zhou, Yan; Wei, Tiantian; Huang, Hongyao (Frontiers in Genetics, 2024)
Background: Dysferlinopathy is an autosomal recessive disorder caused by mutations in the DYSF gene. This study reported two homozygous adjacent missense mutations in the DYSF gene, presenting clinically with bilateral lower limb weakness and calf swelling. Two homozygous adjacent missense mutations in the DYSF gene may be associated with the development of dysferlinopathy, but the exact mechanism needs further investigation. Methods: A retrospective analysis of clinical data from a dysferlinopathy-affected family was conducted. Peripheral blood samples were collected from members of this family for whole-exome sequencing (WES) and copy number variation analysis. Sanger sequencing was employed to confirm potential pathogenic variants. The Human Splicing Finder, SpliceAI, and varSEAK database were used to predict the effect of mutations on splicing function. The pathogenic mechanism of aberrant splicing in dysferlinopathy due to two homozygous adjacent missense mutations in the DYSF gene was determined by an in vivo splicing assay and an in vitro minigene assay. Results: The proband was a 42-year-old woman who presented with weakness of the lower limbs for 2 years and edema of the lower leg. Two homozygous DYSF variants, c.5628C>A p. D1876E and c.5633A>T p. Y1878F, were identified in the proband. Bioinformatics databases suggested that the mutation c.5628C>A of DYSF had no significant impact on splicing signals. Human Splicing Finder Version 2.4.1 suggested that the c.5633A>T of DYSF mutation caused alteration of auxiliary sequences and significant alteration of the ESE/ESS motif ratio. VarSEAK and SpliceAI suggested that the c.5633A>T of DYSF mutation had no splicing effect. Both an in vivo splicing assay and an in vitro minigene assay showed two adjacent mutations: c.5628C>A p. D1876E and c.5633A>T p. Y1878F in the DYSF gene leading to an Exon50 jump that resulted in a 32-aa amino acid deletion within the protein. Point mutation c.5628C>A p. D1876E in the DYSF gene affected splicing in vitro, while point mutation c.5633A>T p. Y1878F in the DYSF gene did not affect splicing function. Conclusion: This study confirmed for the first time that two homozygous mutations of DYSF were associated with the occurrence of dysferlinopathy. The c.5628C>A p. D1876E mutation in DYSF affected the splicing function and may be one of the contributing factors to the pathogenicity.